Estimation of genetic parameters of yield and yield traits in wheat genotypes under rainfed conditions - Khan, Imran; Mohammad, Fida; Khan, Fahim Ullah (International Journal of Environment, 2015)
Development of superior crop varieties is the prime objectives of all plant breeding programs. To determine genetic variability, heritability and genetic advance, 24 elite bread wheat lines were planted in randomized complete block design with three replications at the University of Agriculture, Peshawar under rainfed conditions. Data were recorded on days to heading, days to maturity, plant height (cm), flag leaf area (cm-2), spike length (cm), grain yield (kg ha-1), biological yield (kg ha-1), 1000 grain weight (g), grains spike-1, grain weight spike-1(g), and harvest index (%). Analysis of variance revealed significant differences among genotypes for all the traits studied. Broad sense heritability was high for days to heading (0.89), grain weight spike-1(0.61g), spike length (0.70 cm), 1000-grain weight (0.62g), grain yield (0.78 kg ha-1) and harvest index (0.62%); and was moderate for days to maturity (0.52), plant height (0.38 cm), and grains spike-1 (0.49), while low heritability was estimated for spike weight (0.25g), flag leaf area (0.28 cm-2) and biological yield (0.25 kg ha-1). The values of genetic advance for days to heading, days to maturity, plant height, spike length, grains spike-1, grain weight spike-1, 1000-grain weight, grain yield, biological yield, flag leaf area, and harvest index were; 5.47, 1.88, 4.01, 6.42, 0.16, 5.02, 0.71, 418.83, 379.64, 2.89 and 3.92, respectively. Genotype PR 105 surpassed all other genotypes in grain yield (3144.33 kg ha-1) and hence it can be recommended for rainfed area. DOI: http://dx.doi.org/10.3126/ije.v4i2.12637 International Journal of Environment Vol.4(2) 2015: 193-205